(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes methods of determining the amount of free amino acids in the above-ground part of two types of wild horsetail - Equisetum Arvense L. - field horsetail and Equisetum Ramosissimum D. - field horsetail. The results were presented in tabular form. Amino acids were studied using the Steven A. Cohen Daviel method using high-performance liquid chromatography (HPLC).